THE EFFECTIVENESS OF USING YOUTUBE VIDEO ON EFL IRAQI COLLEGE STUDENTS' PERFORMANCE IN GRAMMAR AT MISSAN UNIVERSITY - Almoswai, Fatima Rahim; Rashid, Bushra Ni’ma (PEOPLE: International Journal of Social Sciences, 2017)
YouTube is a social media platform that was launched in 2005 that allows billions of individuals to discover watch and share original user created videos. YouTube is a powerful educational and motivational tool that is being used in the EFL classroom (Duffy, 2007:173). This study aims to identify and classify the effectiveness of using YouTube Video on EFL Iraqi college students' Performance in Grammar at Missan University. The study is restricted to students (males and females) of the third year EFL Iraqi College students during the academic year 2014-2015. A questionnaire for students and a grammar test have been constructed to be the main instruments used. The result shows that there is a statistically significant difference between the pre and post administration of the questionnaire and in favour of the post administration of the questionnaire.